The effects of two foraging traits on within-plant foraging efficiency of Phytoseiulus persimilis (Acari: phytoseiidae) - Smith, Ian A. (Kansas State University, 2011)
Many crops grown in greenhouses are damaged by the twospotted spider mite, Tetranychus urticae. The predatory mite, Phytoseiulus persimilis, is a commercially-available predator that is commonly used to control twospotted spider mites on greenhouse crops; but its efficacy varies among crops, and it is generally ineffective at low prey densities. In general, predator foraging efficiency depends on how well predators find prey patches, the length of stay in prey patches, and consumption of prey while in prey patches. With respect to P. persimilis, I asked how this predator responds to different prey distributions, as might be encountered at different stages of spider mite infestations. I also asked how components of foraging, namely consumption rate and dispersal tendency, affected predator efficiency. To examine the former, I established T. urticae eggs on 6-leafed cucumber plants in two distributions. To examine the latter, I imposed artificial selection on a population of P. persimilis to create a line that exhibited extremely high consumption and one that demonstrated a greater tendency for dispersal. Subsequently, foraging efficiency was assessed by observing predator oviposition and consumption of twospotted mite eggs on individual leaves of 6-leafed cucumber plants. The number of eggs laid by predators corresponded to the number of prey consumed regardless of predator line. In addition, predators from both lines distributed their eggs proportional to where they fed. However, prey consumption differed between selected lines in response to prey distribution. Predators selected for high consumption fed more on the basal leaf where they were released; whereas prey consumption by the high dispersal and control lines were more evenly distributed throughout the plant. These results contribute to a better understanding of how foraging behavior is modified in plant landscapes under different levels of expression of foraging traits. They also indicate that predator release strategies likely would need to modified in accordance with the kind of foraging trait(s) used in artificial selection programs. In general, my research, when combined with future studies at a broader landscape level, will facilitate decisions by biological control practitioners about whether changes in foraging efficiency resulting from artificial selection justify the cost investment of producing selected lines of P. persimilis
Keywords: Foraging; Selection; Predatory Mites; Twospotted Mites; Patches; Agriculture, General (0473); Entomology (0353)